The difference of human gut microbiome in colorectal cancer with and without metastases - Sun, Leitao; Zhu, Zhenzheng; Jia, Xinru; Ying, Xiangchang; Wang, Binbin; Wang, Peipei; Zhang, Shuo; Yu, Jieru (Frontiers in Oncology, 2022)
Metastasis of colorectal cancer is deemed to be closely related to the changes in human gut microbiome. The purpose of our study is to distinguish the differences of gut microbiota between colorectal cancer with and without metastases. Firstly, patients with colorectal cancer who met the established criteria and healthy volunteers were recruit in this study in the Oncology Department of Zhejiang Hospital of Traditional Chinese Medicine from February 2019 to June 2019. Fresh stool samples from healthy volunteers, non-metastatic patients and metastatic patients were collected for 16S rRNA gene sequencing to analysis both the diversity and abundance of intestinal microorganisms in each group. The results showed that the microbial composition of the Control group was better than the experimental group, while the difference also happen in Tumor and the Metastasis group. At the phylum level, the abundance of Bacteroidetes was significantly declined in the Tumor and the Metastasis group, compared with the Control group. At the class level, Bacilli increased in experimental groups, while the abundance of it was significantly higher in the Tumor group than the Metastasis group. At the order level, the Tumor group had the highest abundance of Lactobacillales, followed by Metastasis group and Control group had the lowest abundance. Overall, our study showed that the composition of the flora changes with the occurrence of metastasis in colorectal cancer. Therefore, the analysis of gut microbiota can be served as a supplement biological basis for the diagnosis and treatment of metastatic colorectal cancer which may offer the potential to develop non-invasive diagnostic tests.